Difficulties of teachers of English to publish scientific articles in peripheral contexts: Perceptions from authors and reviewers - Cárdenas Beltrán, Melba Libia (Íkala, Revista de Lenguaje y Cultura, 2019)
Publishing articles in scientific or academic journals is a big professional challenge and a requirement for most university teachers. This article reports on the difficul-ties faced by some teachers of English to get published in a journal, as found in an exploratory case-study that sought to identify their experiences during the review-ing of their manuscripts. Data were collected through a questionnaire answered by 73 authors and 17 evaluation forms of articles either rejected or containing observations regarding changes required by the reviewers. Complementary infor-mation was also taken from the editorial processes concerning those articles under evaluation. The results show the problems found by the authors, how they solved them, and the critical aspects found by the reviewers. They also allow the iden-tification of implications for the teacher career and for the editorial processes of scientific or periodical publications.